2007
DOI: 10.1080/15287390701252717
|View full text |Cite
|
Sign up to set email alerts
|

Metabolite Profiling of [14C]hexahydro-1, 3, 5-trinitro-1,3,5-triazine (RDX) in Yucatan Miniature Pigs

Abstract: The study reported herein examined the metabolism of 14C-labeled hexahydro-1,3,5-trinitro-1,3,5-triazine (RDX) resulting from a single oral gavage of 5 ml/kg to male and female Yucatan miniature pigs (43 mg/kg, 56 microCi/kg in 0.5% carboxymethylcellulose in water). Blood, urine, and feces were collected at selected times of 1, 6, 12, and 24 h postdose. At 24 h postdose, liver samples were collected. Blood, plasma, liver, and excreta were analyzed for total RDX-derived radioactivity and metabolites were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 10 publications
0
15
0
1
Order By: Relevance
“…A study performed in pigs fed 43 mg/kg of RDX found 2 other metabolites in the urine; 1‐nitrosos‐3, 5‐dinitro‐13,5 triazacyclohexane (MNX) and 1‐nitro‐3, 5 dinitroso‐1,3,5‐triazacyclohexane (DNX). It is unknown at this time if these metabolites cause renal damage 7 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study performed in pigs fed 43 mg/kg of RDX found 2 other metabolites in the urine; 1‐nitrosos‐3, 5‐dinitro‐13,5 triazacyclohexane (MNX) and 1‐nitro‐3, 5 dinitroso‐1,3,5‐triazacyclohexane (DNX). It is unknown at this time if these metabolites cause renal damage 7 …”
Section: Discussionmentioning
confidence: 99%
“…It is unknown at this time if these metabolites cause renal damage. 7 Working dogs, especially those that are exposed to explosive materials are at risk of ingesting C-4. During the training period, the explosive may not be completely packaged in order for the scent to be as potent as possible.…”
Section: Discussionmentioning
confidence: 99%
“…The major route of elimination was through urine in Yucatan miniature pigs. The analysis of liver samples by HPLC showed no parent compound RDX and no metabolites were detected (Major et al 2007).…”
Section: Measurements Of Rdx In the Environmentmentioning
confidence: 98%
“…The widespread use of RDX and HMX after World War II has resulted in their presence in at least 16 of the 1397 hazardous waste sites on the National Priorities List [24], and they are found as pollutants in soil [25,26] and the air [27] around or near munitions manufacturing sites. In mammals, the clinical outcome of oral administration of RDX is the rapid onset of seizures (skeletal muscle convulsions) and increased salivation in humans [28], rats [29][30][31], mice [32], pigs [33], northern bobwhite quail [34], and western fence lizards [35]. Recently, evidence that RDX binds to the γ-aminobutyric acid type A receptor (GABA A R) instead of the NMDAR was presented [36].…”
Section: Introductionmentioning
confidence: 99%